2004
DOI: 10.1039/b312188g
|View full text |Cite
|
Sign up to set email alerts
|

The observation of a large gauche preference when 2-fluoroethylamine and 2-fluoroethanol become protonated

Abstract: The energies of the gauche and anti conformers of 2-fluoroethylamine, 2-fluoroethanol and their protonated analogues are calculated using density functional theory. Unlike the non protonated systems, the protonated systems show a strong gauche effect where the C-F and the C-(+)NH(3) or C-F and C-(+)OH(2) bonds are gauche rather than anti to each other. Single crystal X-ray diffraction studies of 2-fluoroethylammonium compounds identify the same conformational preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 22 publications
4
82
0
Order By: Relevance
“…This value is typical of the stabilisation imparted by antiperiplanar hyperconjugative σ C-H → σ* C-F and σ C-H → σ* C-N interactions, in preference to σ C-N → σ* C-F and σ C-F → σ* C-N . Similar stereoelectronic gauche effects in NCCF systems have previously been described for imines, [44] amines, [6,[45][46][47] and amides. [6,48] Free NHCs and their precursor cations therefore follow the pattern found in other NCCF systems as far as the gauche preference is concerned.…”
Section: Compoundmentioning
confidence: 59%
See 1 more Smart Citation
“…This value is typical of the stabilisation imparted by antiperiplanar hyperconjugative σ C-H → σ* C-F and σ C-H → σ* C-N interactions, in preference to σ C-N → σ* C-F and σ C-F → σ* C-N . Similar stereoelectronic gauche effects in NCCF systems have previously been described for imines, [44] amines, [6,[45][46][47] and amides. [6,48] Free NHCs and their precursor cations therefore follow the pattern found in other NCCF systems as far as the gauche preference is concerned.…”
Section: Compoundmentioning
confidence: 59%
“…The magnitude of this stabilisation is characteristic of an electrostatic gauche effect, which orients the partially negatively charged fluorine preferentially towards the cationic moiety, similarly to the situation seen in N-(2-fluoroethyl)iminium, [7a] -pyridinium, [45] or -ammonium [6,46,47] systems. The Hirshfeld partial charges for 23 (which are practically independent of the torsion angle) are -0.13e (F), 0.00 (both N), and +0.24e (C carb H).…”
Section: Compoundmentioning
confidence: 95%
“…Both conformers A and C maximise attractive gauche interactions between C-F and C-O acceptor bonds and potential donors, whereas both bisected conformations contain a pair of acceptor bonds in an antiperiplanar arrangement. 46 It is possible that the theory used has failed to account adequately for the potential magnitude of this effect. The calculated coupling constant for 17a type C (26.4 Hz) agrees quite well with the measured value, whereas the value calculated using the observed molecular structure in the crystal is rather lower (23.5 Hz).…”
Section: Conformational Analysismentioning
confidence: 99%
“…It is generally found that the trans conformer is more stable than the gauche form and this is due to steric hindrance in the gauche conformation [2]. However fluorine has strong stereoelectronic and polar effects on the conformers of fluorine substituted molecules [3][4][5][6][7][8]. The net effect is that the gauche conformer is unusually more stable for the fluoro substituted conformers and this has been associated with the "gauche effect" [2,9].…”
Section: Introductionmentioning
confidence: 99%